What Is Known about the Immune Response Induced by Plasmodium vivax Malaria Vaccine Candidates? - López, Carolina; Yepes-Pérez, Yoelis; Hincapié-Escobar, Natalia; Díaz-Arévalo, Diana; Patarroyo, Manuel A. (Frontiers in Immunology, 2017)
Malaria caused by Plasmodium vivax continues being one of the most important infectious diseases around the world; P. vivax is the second most prevalent species and has the greatest geographic distribution. Developing an effective antimalarial vaccine is considered a relevant control strategy in the search for means of preventing the disease. Studying parasite expressed proteins which are essential in host cell invasion has led to identifying the regions recognised by individuals who are naturally exposed to infection. Furthermore, immunogenicity studies have revealed that such regions can trigger a robust immune response which can inhibit sporozoite (haepatic stage) or merozoite (erythrocyte stage) invasion of a host cell and induce protection. This review provides a synthesis of the most important studies to date concerning the antigenicity and immunogenicity of both synthetic peptide and recombinant protein candidates for a vaccine against malaria produced by P. vivax.